Since triangle DEF = triangle JKL, m<D = m<J, m<E = m<K, m<F = m<L.
m<F = m<L = 90 degrees
m<K = m<E = 5(m<D)
but m<E + m<D = 90 degrees [right angled triangle]
5(m<D) + m<D = 90 degrees
6(m<D) = 90 degrees
m<D = 90 / 6 = 15 degrees.
For b on the first paper you will start with the distribution property and multiply both x and 2 by 3 because they are in the ()
now you have 3x+ 6=x-18
from here you can subtract x from both sides
2x+6=-18
next subtract 6 from both sides
2x=-24
divide both sides by 2...
x=-12
hope this helped
Answer:
The answer is 15,008 you clicked the right one.
Step-by-step explanation: